Prioritizing Offenders: An Evaluation of the Charlotte-Mecklenburg Police Department POST Program - Lail, Derrick Wesley (2011)
In April 2008, the Charlotte-Mecklenburg Police Department implemented an offender-driven initiative designed to identify those offenders believed to be most actively motivated to commit Part I crimes against the residents of Charlotte, North Carolina. Through a comprehensive and collaborative effort, this approach sought to prioritize available resources in a manner which would hold these identified offenders accountable for their crimes and, ultimately, contribute to a reduction in Charlotte’s persistently high Part I crime. This intervention is known as the Priority Offender Strategy Team (POST). The current study illuminated various weaknesses in the actual implementation process of the POST program; however, statistically significant evidence was produced which demonstrates the program’s ability to reduce recidivism by the identified motivated offenders. The author concluded that the combined support of existing literature and empirical findings allow the CMPD POST program to be considered an effective crime reduction strategy